Study On The Effectiveness Of Supervision And Council By Regional Supervisory Assembly Against Notaries In Gorontalo District - Ridho cahya Pratama Lahay (Estudiante Law Journal, 2020)
The purpose of this article is to determine the effectiveness of the authority of Supervision and Guidance by the Regional Supervisory Board for the Notary profession and to know the inhibiting factors for Supervision and Guidance of the Notary profession in Gorontalo Regency, Although routinely in carrying out supervisory and coaching duties, the Regional Supervisory Council still finds several problems regarding the code of ethics of the notary profession, frequent administrative violations related to the notary deed .The research method used is the empirical legal research method. The problem in this article is to what extent is the effectiveness of the authority of the Regional Supervisory Council towards the supervision and guidance of Notaries in Gorontalo Regency and what are the inhibiting factors in carrying out such supervision and guidance. The results of the discussion show that there are some ineffective supervision implementations such as Notaries in Gorontalo Regency still often neglect to make book bundles if the number of deeds has fulfilled 50 deeds, there are also repeated omissions by Notaries related to the neatness of deed storage and deed picking tests. . The inhibiting factor is the lack of infrastructure due to the combination in 1 Supervisory Council at the regional level so that it has implications for less effective and maximum supervision and guidance for Notaries. For this reason, it is necessary to add authority to the Regional Supervisory Council in the Law on Notary Positions or in other technical regulations as well as the need for government efforts to support human resources in order to increase the Notary profession in Gorontalo, so that with the adequate allocation of the Notary profession in each region, an institution can be created. Regional Supervisors in each of the regions in need.Keywords: Effectiveness, Supervision, Guidance, Notary Position